Parental non-inherited HLA resistance alleles do not confer protection against multiple sclerosis. - Ramagopalan, S; Dyment, D; Herrera, B; DeLuca, G; Lincoln, MR; Orton, S; Handunnetthi, L; Chao, M; Dessa Sadovnick, A; Ebers, G (2008)
Multiple sclerosis (MS) is a complex trait in which alleles at or near the class II loci HLA-DRB1 and HLA-DQB1 contribute significantly to genetic risk. HLA-DRB1*14 and DRB1*11 bearing haplotypes protect against MS and DRB1*01 and DRB1*10 interact with DRB1*15 to reduce risk of the disease. Recent work in other autoimmune diseases such as rheumatoid arthritis has suggested that maternal non-transmitted protective alleles can also confer disease resistance. In this investigation of 7093 individuals from 1432 MS families, we have analysed the transmission of HLA-DRB1*14,*11,*10 and *01 haplotypes, stratified by sex of parent. No significant transmission differences between mothers and fathers were found, suggesting that non-inherited resistance alleles do not appear to play a role in MS.